Protecting the hand that feeds us: Seagrass (Zostera marina) serves as commercial juvenile fish habitat - Chiara Bertelli (Marine Pollution Bulletin, 2014)
Although fisheries are of major economic and food security importance we still know little about specific juvenile habitats that support such production. This is a major issue given the degradation to and lack of protection afforded to potential juvenile habitats such as seagrass meadows. In the present study we investigate the role of seagrass in supporting juvenile fish of commercial value. By assessing seagrass relative to adjacent sand we determined the presence of abundant juvenile fish. Nine commercial species were recorded and the most abundant of these were Plaice, Pollock and Herring. We provide the first quantitative evidence of the presence of juvenile fish of commercial value in seagrass surrounding Great Britain. Although the species that we found in seagrass as juveniles are not obligate seagrass users the resources that seagrass meadows offer to these fish provide significant long-term fitness benefits, potentially enhancing the whole population.